Trauma surgical skill sustainment at the University of Chicago AMEDD Military-Civilian Trauma Team Training Site: an observation report - Priya Prakash; Kenneth Wilson; Jennifer Cone; Selwyn O Rogers; Andrew Benjamin; Timothy P Plackett; Nicholas Jaszczak; David A Hampton (Trauma Surgery & Acute Care Open)
Background The Army Medical Department (AMEDD) Military-Civilian Trauma Team Training (AMCT3) Program was developed to enhance the trauma competency and capability of the medical force by embedding providers at busy civilian trauma centers. Few reports have been published on the outcomes of this program since its implementation.Methods The medical and billing records for the two AMCT3 embedded trauma surgeons at the single medical center were retrospectively reviewed for care provided during August 2021 through July 2022. Abstracted data included tasks met under the Army’s Individual Critical Task List (ICTL) for general surgeons. The Knowledge, Skills, and Abilities (KSA) score was estimated based on previously reported point values for procedures. To assess for successful integration of the embedded surgeons, data were also abstracted for two newly hired civilian trauma surgeons.Results The annual clinical activity for the first AMCT3 surgeon included 444 trauma evaluations and 185 operative cases. The operative cases included 80 laparotomies, 15 thoracotomies, and 15 vascular exposures. The operative volume resulted in a KSA score of 21 998 points. The annual clinical activity for the second AMCT3 surgeon included 424 trauma evaluations and 194 operative cases. The operative cases included 92 laparotomies, 8 thoracotomies, and 25 vascular exposures. The operative volume resulted in a KSA score of 22 799 points. The first civilian surgeon’s annual clinical activity included 453 trauma evaluations and 151 operative cases, resulting in a KSA score of 16 738 points. The second civilian surgeon’s annual clinical activity included 206 trauma evaluations and 96 operative cases, resulting in a KSA score of 11 156 points.Conclusion The AMCT3 partnership at this single center greatly exceeds the minimum deployment readiness metrics established in the ICTLs and KSAs for deploying general surgeons. The AMEDD experience provided a deployment-relevant case mix with an emphasis on complex vascular injury repairs.